2002
DOI: 10.1046/j.1365-3083.2002.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Coupling of Palmitate to Ovalbumin Inhibits and Blocks the Induction of Oral Tolerance*

Abstract: Oral tolerance is a phenomenon that may occur in animals exposed to soluble antigens for the first time by the oral route. In the present study, we show that oral tolerance against ovalbumin (Ova) can be obtained after intragastric administration of the antigen in the presence of free residues of palmitate. On the other hand, oral tolerance induction is blocked when the residues of palmitate are covalently bound to the antigen (Ova-palmitate conjugates). We have also noticed that oral administration of Ova-pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Cell culture was performed as previously described (Oliveira et al 2002). Splenocytes (5 × 10 6 cells/mL) were cultured in complete medium (RPMI 1640; Sigma) supplemented with 2 mM Lglutamine (Sigma), 1 mM sodium pyruvate (Sigma), 5 × 10 −5 M 2-mercaptoethanol (MerckSchuchardt, Müchen, Germany), 50 penicillin IU/mL, and 10% heat-inactivated fetal calf serum (FCS-Interlab, São Paulo, Brazil).…”
Section: Cellular Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell culture was performed as previously described (Oliveira et al 2002). Splenocytes (5 × 10 6 cells/mL) were cultured in complete medium (RPMI 1640; Sigma) supplemented with 2 mM Lglutamine (Sigma), 1 mM sodium pyruvate (Sigma), 5 × 10 −5 M 2-mercaptoethanol (MerckSchuchardt, Müchen, Germany), 50 penicillin IU/mL, and 10% heat-inactivated fetal calf serum (FCS-Interlab, São Paulo, Brazil).…”
Section: Cellular Proliferationmentioning
confidence: 99%
“…It has been previously shown that the coupling of palmitoyl residues to Ova abolished the induction of oral tolerance in B6D2F1 mice (Oliveira et al 1998;Oliveira et al 2002). To determine whether this coupling might influence the activation of APCs, cells from PerC were cultured with Ova or palmitoyl-Ova at two different concentrations and evaluated for the expression of activation markers.…”
Section: Evaluation Of the Expression Of Costimulatory Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ethanol can alter the morphology and physiology of the intestinal wall, promote serious damage to the gastric mucosa by destroying 10-50% of villi and enhance intestinal permeability (Andrade et al 2006;Beck et al 1996). A previous study had shown that palmitoyl-ovalbumin (palmitoyl-ova), not the naïve ova, was efficient in generating the humoral and cellular immunity (Oliveira et al 2002). Palmitoyl-ova also stimulated the production of IgA antibodies (Oliveira et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study had shown that palmitoyl-ovalbumin (palmitoyl-ova), not the naïve ova, was efficient in generating the humoral and cellular immunity (Oliveira et al 2002). Palmitoyl-ova also stimulated the production of IgA antibodies (Oliveira et al 2002). By contrast, the levels of IgA antibodies were lower in the intestinal fluid from ethanol-treated mice (Gusmão et al 2004); however, systemic immunization and oral tolerance against palmitoyl-ova and ova, respectively, were not affected by ethanol (Gusmão et al 2004).…”
Section: Introductionmentioning
confidence: 99%